1995
DOI: 10.1002/bin.2360100302
|View full text |Cite
|
Sign up to set email alerts
|

Antecedent exercise as a treatment for disruptive behavior: Testing hypothesized mechanisms of action

Abstract: This study evaluated the effects of antecedent physical exercise (AE) and a mastery task on behaviorally disturbed children's self-concepts and rates of disruptive behaviors. In addition, we evaluated whether changes in self-concept mediated any exercise induced changes in rates of disruptive behavior. Fifty-eight children were randomly assigned to one of three conditions: (a) antecedent exercise (jog/walk), (b) "mastery" task (a successive improvement miniaturebasketball shooting task), and (c) no treatment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Their failure to include a control group and the high risk of bias in this study, make it difficult to interpret the intervention effects. Alternatively, the fitness programme evaluated by Basile et al (1995) did not improve self-concept in a group of children with behavioural disorders. The fitness programme consisted of jogging and walking around the school playground for 20 min.…”
Section: Physical Fitness Programmesmentioning
confidence: 94%
See 4 more Smart Citations
“…Their failure to include a control group and the high risk of bias in this study, make it difficult to interpret the intervention effects. Alternatively, the fitness programme evaluated by Basile et al (1995) did not improve self-concept in a group of children with behavioural disorders. The fitness programme consisted of jogging and walking around the school playground for 20 min.…”
Section: Physical Fitness Programmesmentioning
confidence: 94%
“…Our search identified 15 studies that evaluated the effects of physical activity programmes on social and emotional well-being in at-risk children and adolescents (Table 1). Seven studies evaluated the effects of outdoor adventure programmes (Bloemhoff, 2006;Cross, 2002;Green, Kleiber, & Tarrant, 2000;Kaiser, Smith, Heleski, & Spence, 2006;Minor & Elrod, 1994;Pommier & Witt, 1995;Wu & Hsieh, 2006), seven studies evaluated the effects of sport and skill-based interventions (Basile, Motta, & Allison, 1995;Bonnette, McBride, & Tolson, 2001;Goodway & Rudisill, 1996;Maiano, Ninot, Morin, & Bilard, 2007;Palermo et al, 2006;Robinson et al, 2009;Tester, Watkins, & Rouse, 1999) and two studies reported the effects of physical fitness programmes (Basile et al, 1995;Collingwood, Sunderlin, & Kohl, 1994). The majority of studies evaluated the effects of programmes among older children and adolescents, however, two studies (Goodway & Rudisill, 1996;Robinson et al, 2009) reported the effects of motor skill interventions in at-risk preschool children.…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations